The Mencué Batholith: Permian episodic arc-related magmatism in the western North Patagonian Massif, Argentina. Issue 3 (11th February 2021) - Gregori, Daniel A.; Strazzere, Leonardo; Barros, Mercedes; Benedini, Leonardo; Marcos, Paulo; Kostadinoff, José
ABSTRACT: The Mencué Batholith, western North Patagonian Massif, includes three major bodies. The Mencué Granodiorite, Cura Lauquén Granite and La Blancura Syenogranite. There are dikes of granitic and basaltic rocks cutting the above-cited rocks. The Mencué Batholith represents several episodes of magmatism, with ages varying between 294 and 239 Ma. The Mencué Granodiorite and the Cura Lauquén Granite are solid-state deformed and are S-type. They have high-K and normal calc-alkaline affinities. These rocks contain significant quantities of subduction-zone chemical components that decrease towards younger lithofacies. La Blancura Syenogranite lack subduction zone chemical components and represent A-type granite, typical of within-plate magmatism. The partial melting of metapelites could be the process of formation of these bodies. The older lithofacies of the Mencué Batholith, found westernmost, display a stronger deformation, but there is a progressive eastward change to younger and mildly deformed bodies and even non-deformed bodies. We conclude that the evolution of the Mencué Batholith start in the Sakmarian-Roadian (Early Permian) period. At this time, a subduction zone was active to the west and its thermal influence affected sedimentary or metamorphic rocks producing S-type granites During the Wordian and Capitanian, (Middle Permian) periods, the Mencué Batholith was mildly deformed, possibly in the process of the vanishing of the deformation and has a minor subduction chemical signature. Between the Wuchiapingian and Olenekia periods, the alkaline facies of the Mencué Batholith show an absence of deformation and the characteristics of within-plate magmatism. The Early Permian magmatic events in the western North Patagonian Massif are represented by the older bodies of the Mencué Batholith and were produced by subduction in the western margin of the Gondwanan continent. The Late Permian-Early Triassic magmatic events show a noticeable decreasing influence of subduction and an increasing influence of within-plate chemical components. Graphical Abstract: